2016
DOI: 10.1186/s13195-016-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

The pre-synaptic vesicle protein synaptotagmin is a novel biomarker for Alzheimer’s disease

Abstract: BackgroundSynaptic degeneration is a central pathogenic event in Alzheimer’s disease that occurs early during the course of disease and correlates with cognitive symptoms. The pre-synaptic vesicle protein synaptotagmin-1 appears to be essential for the maintenance of an intact synaptic transmission and cognitive function. Synaptotagmin-1 in cerebrospinal fluid is a candidate Alzheimer biomarker for synaptic dysfunction that also may correlate with cognitive decline.MethodsIn this study, a novel mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 145 publications
(117 citation statements)
references
References 40 publications
4
110
2
1
Order By: Relevance
“…SYT1 is a member of a synaptotagmin (syt) family, who plays a critical role in the release of neurotransmitters from presynaptic nerve terminals (Yoshihara & Montana, ). It has been reported that SYT1 was required for rapid neurotransmitter release in mouse hippocampal neurons (Evans, Ruhl, & Chapman, )and was decreased in several brain regions and increased in cerebrospinal fluid of patients with Alzheimer's disease (Ohrfelt et al, ; Yoo, Cairns, Fountoulakis, & Lubec, ). Consequently, SYT1 was selected from the predicted targets of miR‐34c for further validation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…SYT1 is a member of a synaptotagmin (syt) family, who plays a critical role in the release of neurotransmitters from presynaptic nerve terminals (Yoshihara & Montana, ). It has been reported that SYT1 was required for rapid neurotransmitter release in mouse hippocampal neurons (Evans, Ruhl, & Chapman, )and was decreased in several brain regions and increased in cerebrospinal fluid of patients with Alzheimer's disease (Ohrfelt et al, ; Yoo, Cairns, Fountoulakis, & Lubec, ). Consequently, SYT1 was selected from the predicted targets of miR‐34c for further validation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported elevated CSF levels of individual synaptic proteins such as neurogranin (8), SNAP-25 (9), synaptotagmin-1 (10) in AD dementia patients and neurexins 1, 2 and 3, and neurofascin (11) in prodromal AD patients. Although these findings support the idea that synaptic proteins in CSF may be informative in AD, the previously reported correlation between CSF levels of synaptic proteins with CSF levels of tau suggest that widespread neuronal loss could be a confounding factor when studying synaptic proteins in the CSF, particularly at clinical disease stages.…”
Section: Graphical Abstract Highlightsmentioning
confidence: 90%
“…; Ohrfelt et al . ). SNAP‐25 and synaptotagmin‐1 are both brain‐enriched proteins involved in vesicular trafficking.…”
Section: Biomarkers For Synaptic Degenerationmentioning
confidence: 97%